Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.alcohol.2009.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of alcohol consumption and its effect on gastrointestinal symptoms in inflammatory bowel disease

Abstract: Alcohol consumption is a potential trigger for flare in Inflammatory Bowel Disease (IBD) flare because of alcohol’s pro-oxidant effects and its deleterious effects on gut barrier function. The association with alcohol consumption and IBD flare is unclear. To test this hypothesis, we evaluated the pattern of alcohol consumption and its self-reported effect on gastrointestinal (GI) symptoms in patients with IBD. We recruited 129 consecutive patients: 52 patients with Crohn’s Disease, 38 patients with Ulcerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 24 publications
4
66
5
2
Order By: Relevance
“…Some studies have shown that alcohol impairs symptoms [14], whereas others have shown that alcohol has no effect on functional gastrointestinal symptoms [12]. Alcohol may trigger relapses and pronounced symptoms in patients with already developed IBD [36], which could not be seen in our study for the MC patients. The effect measured on symptoms reasonably has to be connected to the volume consumed.…”
Section: Patients With Irritable Bowel Syndromecontrasting
confidence: 71%
“…Some studies have shown that alcohol impairs symptoms [14], whereas others have shown that alcohol has no effect on functional gastrointestinal symptoms [12]. Alcohol may trigger relapses and pronounced symptoms in patients with already developed IBD [36], which could not be seen in our study for the MC patients. The effect measured on symptoms reasonably has to be connected to the volume consumed.…”
Section: Patients With Irritable Bowel Syndromecontrasting
confidence: 71%
“…Indeed, previous studies have already demonstrated that alcohol is a common exposure in patients with IBD, and it is consumed in proportion to the general population [13]. There is no doubt that hazardous/harmful alcohol use (defined as consumption of greater than 40 g of alcohol per day for men and 20 g for women) [26] has numerous deleterious health effects on other organ systems like the liver, intestine, and immune system and incurs annual health costs of USD 100 billion in the United States [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another study in CD found no difference in alcohol absorption or abdominal pain from five different alcoholic drinks [12], and concluded that it is likely the high sugar content that is responsible for reported symptoms. In addition, we recently reported on a cohort study using a survey analysis of alcohol consumption in inactive IBD, and found that patients with IBD do drink alcohol in a similar pattern to the general population, but were also more likely to report that alcohol worsens their gastrointestinal (GI) symptoms than patients with irritable bowel syndrome [13]. …”
Section: Introductionmentioning
confidence: 99%
“…nursing home admission), be prescribed alcohol-incompatible medications, or receive advice to drink less from healthcare professionals (17)(18)(19)(20). In England 71% adults aged 65 years and older report at least one long-term condition (LTC) (21), and alcohol can worsen the symptoms of LTCs (22), influence self-care behaviours (23) and interact with medications (24).…”
Section: Introductionmentioning
confidence: 99%